2011
DOI: 10.1007/s10792-011-9498-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up and visual outcome after excision of a traumatic iris cyst by viscoelastic dissection

Abstract: To report the long-term follow-up and visual outcome after excision of a traumatic iris cyst. A 4-year-old female presented with an iris cyst in her left eye 2 years after corneal laceration repair. An 8 × 7 mm cyst was located between 1 and 6 O'clock on the iris, extending into the anterior chamber. The cyst was surgically removed by dissection from the endothelium and angle by viscoelastic and was submitted for histopathological examination. Postoperative outcomes including visual acuity (VA) and complicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…The technique of adjuvant use of ophthalmic viscoelastic agent, external surgical drainage of cyst followed by endophotocoagulation was also been reported by Lockington et al [9]. Al-Ghadeer et al also reported the technique and the outcome of viscoelastic dissection of a traumatic iris cyst [10]. In our case, we recommend viscodissection technique as it enables safe separation from surrounding structure.…”
Section: Discussionsupporting
confidence: 69%
“…The technique of adjuvant use of ophthalmic viscoelastic agent, external surgical drainage of cyst followed by endophotocoagulation was also been reported by Lockington et al [9]. Al-Ghadeer et al also reported the technique and the outcome of viscoelastic dissection of a traumatic iris cyst [10]. In our case, we recommend viscodissection technique as it enables safe separation from surrounding structure.…”
Section: Discussionsupporting
confidence: 69%
“…Laser iridotomy of the cyst offers a noninvasive method of therapy for posttraumatic iris inclusion cysts but is associated with a high rate of recurrence 19. Viscoelastic dissection of the posttraumatic iris cyst has been described with an acceptable long-term outcome 20. Viscoelastic-assisted endophotocoagulation has been documented to have an excellent response in the management of secondary iris cysts 21.…”
Section: Discussionmentioning
confidence: 99%
“…Cyst puncture and debulking coupled with aspiration of cyst contents can be attempted with careful attention as to not allow expulsion of contents into the anterior chamber. Viscoelastic dissection of the cyst, cauterization, diathermy, electrolysis, and cryotherapy can also be implemented [ 1 , 29 , 30 , 33 35 ]. Intracystic injections of sclerosing agents or cytotoxic agents such as phenol, saline, iodine, 50% dextrose, ethanol, or mitomycin-C (MMC) can be used to halt cyst growth [ 1 , 36 39 ].…”
Section: Review Of the Literature And Discussionmentioning
confidence: 99%